2016
DOI: 10.16965/ijar.2016.306
|View full text |Cite
|
Sign up to set email alerts
|

Diaphyseal Nutrient Foramen of Lower Limb Long Bones: Variations and Importance

Abstract: Background:The nutrient foramen (NF) is the largest of the foramen present on the shaft of long bone allowing nutrient artery to enter the bone. These arteries are important during active growth period of embryo and fetus and during the early phases of ossification. They provide 70-80% of the interosseous blood to long bones. The context and purpose of the study:The study was conducted on 156 long bones of lower limb available in the department of anatomy, Government medical college, Aurangabad.The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 6 publications
5
15
0
Order By: Relevance
“…Mazengenya et al [14] has reported the occurrence of 6 nutrient foramina on a single femur. Ambekar SA et al [9] has reported the occurrence of 5 nutrient foramina in 2 femur bones and triple nutrient foramina were observed in 26.9% of the femur bones in their study.…”
Section: Femurmentioning
confidence: 70%
See 4 more Smart Citations
“…Mazengenya et al [14] has reported the occurrence of 6 nutrient foramina on a single femur. Ambekar SA et al [9] has reported the occurrence of 5 nutrient foramina in 2 femur bones and triple nutrient foramina were observed in 26.9% of the femur bones in their study.…”
Section: Femurmentioning
confidence: 70%
“…Nutrient foramina which did not allow the passage of a size 24 gauge needle were considered as secondary nutrient foramina. Nutrient foramina which allowed the passage of size 24 gauge needle were considered as dominant nutrient foramina [9]. The direction of the nutrient foramen was assessed by passing a hypodermic needle into the nutrient foramen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations